The Case For An Analytical Construction And Enforcement Of Demand Guarantees In Nigeria - Mayomi, Kolawole (Journal of Sustainable Development Law and Policy, 2025)
Demand guarantees are independent collateral undertakings that secure the beneficiary against losses arising from the risk of default in an underlying contract. However, unlike in a true guarantee, the surety’s liability in a demand guarantee is insulated from disputes arising on the underlying contract as it is triggered by the beneficiary’s mere demand for payment, without any need to establish the principal’s default in the underlying contract. A review of Nigerian law reveals a lack of clarity in the construction and enforcement of demand guarantees, such that the courts have largely adopted a blanket approach which erroneously conflates the principles that undergird true guarantees and demand guarantees, and treats the payment obligation arising in both categories of guarantee contracts as the same. The consequence of this approach is to (a) open up the surety in a true guarantee to a primary liability; or (b) impose an onerous obligation upon the beneficiary in a demand guarantee to establish default in an underlying contract before the undertaking may be enforced. This article discusses the need for an analytical approach to the construction and enforcement of demand guarantees in Nigeria. It examines the key normative strengths of this approach which includes the ‘pay now, argue later’ rule, and proposes practical legal reforms through which the analytical approach could be better recognized by Nigerian courts and in Nigerian laws.